THE RELATIONSHIP BETWEEN EXCLUSIVE BREASTFEEDING AND PSYCHOMOTOR INFANTS 6-9 MONTHS AT BUNTULIA HEALTH CENTER - isma saleh; rahma labatjo; fitriani rahmatismi blongkod (Jurnal Ilmiah dr. Aloei Saboe, 2022)
Problems that often occur in infants in Indonesia are related to exclusive breastfeeding. In this case, exclusive breastfeeding is given directly by the mother. The problem that occurs in some mothers is the perception that an insufficient supply of breast milk which means that the mother has only a small amount of breast milk. This research uses analytic observational research, namely research that explains the relationship between variables through hypothesis testing. The research design is based on a cross sectional study, which is a study that takes samples at the same time. This study aims to determine the relationship between exclusive breastfeeding and psychomotor infants 6-9 months in ​​Buntulia Health Center. A research approach is a quantitative approach because the research data is in the form of numbers and the analysis uses statistics. This research uses analytic observational research, namely research that explains the relationship between variables through hypothesis testing. The research design is based on a cross-sectional study, which is a study that takes samples at the same time. Based on the results of the study, it was found that infants who were exclusively breastfed experienced normal development as many as 17 respondents (70.8%), 7 respondents (29.2%) doubtful development and 0 respondents (0%) deviant development and infants who were not exclusively breastfed. experienced normal development as many as 11 respondents (35.5%) doubtful development as many as 13 respondents (41.9%) and deviant development as many as 7 respondents (22.6).